2020
DOI: 10.1038/s41598-020-74075-z
|View full text |Cite
|
Sign up to set email alerts
|

EEG microstates of dreams

Abstract: Why do people sometimes report that they remember dreams, while at other times they recall no experience? Despite the interest in dreams that may happen during the night, it has remained unclear which brain states determine whether these conscious experiences will occur and what prevents us from waking up during these episodes. Here we address this issue by comparing the EEG activity preceding awakenings with recalled vs. no recall of dreams using the EEG microstate approach. This approach characterizes transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 56 publications
8
51
0
Order By: Relevance
“…Interestingly, we observed highly similar MS topographies (with minimum spatial correlations of r > 0.98) across all investigated broad- and narrow- band frequencies (broadband, delta to beta), as well as between EO/EC conditions. This is compatible with recent work by Brechet and colleagues [27], who observed that states of sleep and wake exhibited significantly different spectral content (e.g. delta vs beta power) but very similar MS maps.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we observed highly similar MS topographies (with minimum spatial correlations of r > 0.98) across all investigated broad- and narrow- band frequencies (broadband, delta to beta), as well as between EO/EC conditions. This is compatible with recent work by Brechet and colleagues [27], who observed that states of sleep and wake exhibited significantly different spectral content (e.g. delta vs beta power) but very similar MS maps.…”
Section: Discussionsupporting
confidence: 93%
“…Figure 1 illustrates the topographic results of MS segmentations in the different conditions and frequency bands. After visual inspection of optimal clusters at different cluster numbers (k), we identified that a value of k=5 revealed five MS topographies that were similar across all EEG bands and behavioural conditions, consistent with recent findings from our laboratory [21], [26], [27]. MS maps were designated in line with the canonical prototypes from the literature and their respective symbols, featuring a left-right orientation (A), a right-left orientation (B), an anterior-posterior orientation (C), fronto-central maximum (D) and occipito-central (C’)maximum.…”
Section: Resultssupporting
confidence: 88%
“…Nevertheless, recent studies raised the question about whether the broad-band activity should be spectrally differentiated in order to identify and describe spatio-temporally overlapping spectral patterns (Javed et al 2019 , 2020 ). A recent study in adults found that during NREM sleep low frequencies dominated in all microstates, whereas the EEG power for high frequencies was higher during wakefulness (Brechet et al 2020 ). Our results confirmed that microstate analysis may be frequency-dependent, and the GEV is higher for lower oscillatory frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Xu et al ( 2020 ) investigated the relationship between fMRI fluctuations and microstates during slow wave sleep, revealing a correlation between EEG microstates and brain functional networks. Recently, Bréchet et al ( 2020 ) compared microstates during NREM sleep with microstates in wakefulness, showing that two microstates dominated sleep, with a different spectral content with respect to the microstates dominating wakefulness. Bréchet and colleagues also highlighted the possibility to characterize functional states of the sleeping brain, such as dreaming experiences, by means of specific dominant microstates.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns are recovered not only on healthy individuals but also on diverse groups of patients (Rieger, Hernandez, Baenninger, & Koenig, 2016), and they are preserved through aging, with modifications in dynamic parameters that are compatible with the different development stages of an individual over time (Koenig et al, 2002). Furthermore, the dynamic modulation of microstates is related to behavior and perception (Britz, Díaz Hernàndez, Ro, & Michel, 2014; Britz & Michel, 2011; Müller et al, 2005; Pedroni et al, 2017), may be affected in some diseases (da Cruz et al, 2020; Dierks et al, 1997; Khanna et al, 2015; Rieger et al, 2016; Strik et al, 1997), by the use of specific medications (Khanna et al, 2015; Kinoshita et al, 1995) and in altered states of consciousness (Bréchet, Brunet, Perogamvros, Tononi, & Michel, 2020; Katayama et al, 2007; Khanna et al, 2015).…”
Section: Introductionmentioning
confidence: 99%